Effectiveness of Problem-Based Learning with GeoGebra on Grade VII Students’ Learning Outcomes in Polyhedra at SMP Negeri 1 Mangarabombang - Hamda; Muhammad Ammar Naufal; Nurwahidah (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2025)
This study aims to asses the effectiveness of the Problem-Based Learning (PBL) model supported by GeoGebra on students’ mathematics attainment in the topic of polyhedra (flat-sided solid figures) among seventh-grade students at SMPN 1 Mangarabombang. This study utilized quasi-experimental study used a nonequivalent control group design with a quantitative approach. The population consisted of all seventh-grade students from ten classes, and cluster random sampling was used to select the sample. As a result, the experimental group (PBL with GeoGebra) was VII Sultan Hasanuddin and class the control group (PBL without GeoGebra) was VII Andi Mappanyukki. Test and observation sheet are used to collect the data, and analyzed using descriptive and inferential statistical methods. The results revealed that the average post-test score in the experimental group reached 83.19, with 100% mastery (31 out of 31 students scoring ≥75), and a normalized gain score reached 0.77 (high category). In contrast, the average post-test score in the control group reached 78.29, with 93.55% mastery (29 out of 31 students scoring ≥75), and a gain score of 0.69 (moderate category). From the independent sample t-test revealed there is a statistically significant difference between the two groups. These findings suggest that incorporating GeoGebra into the PBL model leads to better mathematics learning outcomes compared to PBL without GeoGebra, as evidenced by higher post-test scores, greater mastery rates, and more substantial learning gains.